(untitled) (Web of Teachers: Inderscience Research, 2024)
STEAM is an acronym for Science, Technology, Engineering, and Mathematics. The article provides information about STEAM technologies that are rapidly developing today. The methods of using this technology, as well as the introduction of the first STEAM technology, are discussed.